Ribociclib-induced acute kidney injury in patients with advanced-stage breast cancer: A case series and literature review - Maissoune Hajir; Ramiz Abu-Hijlih; Areej Abu Sheikha; Kholoud Alqasem; Hikmat Abdel-Razeq (Current Problems in Cancer: Case Reports, 2023)
Introduction: The phase-3 MONALEESA-2, -3 and -7 randomized trials showed benefit of CDK4/6 inhibitor, ribociclib, in women with advanced-stage breast cancer. However, ribociclib-induced acute kidney injury (AKI) was not addressed in these studies. In this report, we explore AKI in breast cancer patients receiving ribociclib. Methods: Medical records of all breast cancer patients who received ribociclib at our institution between April 2019 and September 2021 were reviewed. Details of creatinine kinetics in relation to ribociclib administration and other nephrotoxic drugs were obtained. Acute kidney injury grades (AKI-KDIGO classification) were captured. Results: 154 females, with advanced-stage breast cancer treated with aromatase inhibitors (AI) or fulvestrant plus ribociclib were reviewed. A total of 29 (18.8%) patients developed AKI; 5 were grade-I, 21 grade-II and 3 were grade-III. Rate of AKI was significantly higher (n = 16, 45.7%) among 35 patients who were on other concomitant nephrotoxic drugs, compared to 11 (9.6%) of 114 other patients, p = 0.001. Median time to develop AKI was 54 (range, 21–168) days, while the median time for creatinine recovery was 5 (range, 4–7) days after holding the drugs. Average creatinine increment for affected patients was 2.28 times the baseline level. Time to AKI was sooner, but not statistically significant, among patients on nephrotoxic drugs and recovery was faster after stopping these drugs. Conclusion: Ribociclib-induced AKI is not uncommon and not adequately addressed. Though reversible in majority of patients, some patients may develop grade-III AKI or require treatment interruption. Nephrotoxic drugs seem to significantly enhance ribociclib-associated renal injury, withholding these drugs and close follow up is strongly recommended. Prospective studies are warranted to validate these conclusions.